Growth performance and body composition of giant trahira fingerlings fed diets with different protein and energy levels - Veras, Galileu Crovatto; Salaro, Ana Lúcia; Zuanon, Jener Alexandre Sampaio; Carneiro, Antonio Policarpo Souza; Campelo, Daniel Abreu Vasconcelo; Murgas, Luis David Solis (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to determine the proper levels of protein and energy in diets of Hoplias lacerdae fingerlings. The dietary crude protein (CP) and gross energy (GE) levels for fingerlings of giant trahira were evaluated in a completely randomized 4x3 factorial design with 35, 39, 43 and 47% CP and 4,100, 4,300 and 4,500 kcal kg-1 of GE, and four replicates. The survival rate was 99.22%, and a linear improvement on the performance parameters was detected after increasing diet crude protein levels. Feed conversion ratio decreased with increasing levels of dietary protein and energy in the diets. A significant interaction between crude protein and gross energy was observed over body protein and mineral matter. Body lipid has increased linearly as gross energy in the diet increased. The retention of crude protein and energy showed a linear increasing with rising of crude protein levels in the diet. Crude protein level at 47% provides the best performance and energy retention, independently of the gross energy levels in the diet.